Morphological segmentation and analysis of Bangla text - Saha, G C; Saha, Hasi; Che Mat, Ruzinoor; Khan, Nur Hossain; Sarker, Bappa (Faculty of Computing, Universiti Teknologi Malaysia, 2016)
This paper deals with lexicon and system development for word segmentation in Bangla language.Our goal in this paper is to develop a morphological segmentation algorithm that can work well for Bangla and to address the problem of unsupervised word segmentation across different languages.From a hand-corrected Bangla corpus, 5000 popular words were segmented into suffixes, prefixes and roots manually.These were the sample lexicon used as seed for next step. A system was developed using C language to automate the Segmentation process based on hand made lexical database.The System was evaluated on several pages of Bangla text and achieved a success rate of about 83.05%.In our observation the system will work with full success if twice the volume of lexicon database and this system may have a huge impact particularly to learn and use Bangla for the people which will enhance their socio-economic life greatly.